Assessing small-scale raspberry producers' risk and ambiguity preferences: Evidence from field-experiment data in rural Chile - Jorge Cárcamo; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2016)
Most researchers who analyze producers' preferences under uncertainty report that producers are averse towards risk and ambiguity scenarios. This aversion has an influence on producers' decision-making processes; hence the relevance of determining and analyzing these preferences as a key factor to design agricultural policies that help producers to cope with production uncertainty. In this study we elicit small-scale raspberry producers' preferences through field experiments in rural Maule (Chile). In addition, we identify producers' socioeconomic and farm characteristics that influence these preferences. Finally, we compare the two standard methods in the current literature to estimate producers' risk preferences from field experiments, and analyze if the estimation method influences these preferences. Our results show an asymmetry in producers' risk preferences; producers are twice as sensitive to losses as to gains. Additionally, we find that producers get smaller lottery utilities in scenarios where ambiguity is present, which implies ambiguity aversion. We also show that the method used to estimate risk preferences can influence the results, with obvious implications for policy design.
Keywords: 330; Risk Preferences; Ambiguity Preferences; Small-scale Producers; Raspberry Producers; Producers' Preferences Elicitation